2003
DOI: 10.1093/emboj/cdg252
|View full text |Cite
|
Sign up to set email alerts
|

A reducing system of the superoxide sensor SoxR in Escherichia coli

Abstract: The soxRS regulon functions in protecting Escherichia coli cells against superoxide and nitric oxide. When SoxR is activated by oxidation of its [2Fe–2S] cluster, it increases the synthesis of SoxS, which then activates its target gene expression. How the oxidized SoxR returns to and is maintained in its reduced state has been under question. To identity genes that constitute the SoxR‐reducing system, we screened an E.coli mutant library carrying a chromosomal soxSp::lacZ fusion, for constitutive mutants. Muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
171
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(178 citation statements)
references
References 44 publications
7
171
0
Order By: Relevance
“…The resulting mutant strain and the parent EH46 strain were transformed with pSE380-based vectors containing the WT soxR gene or the mutant alleles encoding the proteins mentioned above, and the transcriptionactivating abilities of the various proteins in the two strains was determined by assaying ␤-galactosidase activity from the soxS promoter-lacZ reporter. As previously observed (40), WT SoxR showed significantly higher activity in an rsxC background, which indicates loss of regulation (Fig. 4).…”
Section: Redox Activity Of Soxr [2fe-2s] Centers-supporting
confidence: 85%
See 3 more Smart Citations
“…The resulting mutant strain and the parent EH46 strain were transformed with pSE380-based vectors containing the WT soxR gene or the mutant alleles encoding the proteins mentioned above, and the transcriptionactivating abilities of the various proteins in the two strains was determined by assaying ␤-galactosidase activity from the soxS promoter-lacZ reporter. As previously observed (40), WT SoxR showed significantly higher activity in an rsxC background, which indicates loss of regulation (Fig. 4).…”
Section: Redox Activity Of Soxr [2fe-2s] Centers-supporting
confidence: 85%
“…In this work we also explored the effect of a recently identified reducing system on SoxR (40). The products of the rsx operon and the rseC gene are partially responsible for maintaining SoxR in a reduced state in the absence of oxidative stress (40), although no direct interactions have been identified between any of the gene products and SoxR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Roe and colleagues showed that the rsxABCDGE and rseC genes mediate SoxR reduction (40). They encode membrane-bound proteins that resemble members of the Rhodobacer capsulatus Rnf complex, which drives electrons onto nitrogenase.…”
Section: The Soxr(s) Regulator Of the Response To Superoxide Stressmentioning
confidence: 99%